Prevention of Covid-19 Spread in Kunti Village Bungkal Ponorogo Village Through the Use of Steriles Booths - Anggiya Dwi Nanda; Princess Julianti (Faculty of Education Universitas Negeri Malang, 2020)
The Covid-19 virus pandemic hit the whole world in early 2020. This new virus was first discovered in Wuhan, Hubei Provision, China. Many countries affected by this virus, including Indonesia. The percentage of deaths caused by this virus reaches 9.11. Vaccines for this virus have not yet been found.This inspired the Covid edition of students social works at Universitas Negeri Malang to make a breakthrough in preventing Covid-19 transmission. One of the work programs that shows a breakthrough in preventing Covid-19 transmission is the delivery of sterile booths to the Kunti Village, Bungkal District, Ponorogo. It is hoped that the sterile booth will be able to break the chain of transmission of the Covid-19 virus.